URGENSI PENGATURAN ARTIFICIAL INTELLIGENCE KENDARAAN AUTOPILOT BERDASARKAN HUKUM LALU LINTAS DI INDONESIA - Rafael Yehezkiel Aritonang (Brawijaya Law Student Journal, 2023)
Rafael Yehezkiel Aritonang, Yenny Eta Widyanti, Ranitya Ganindha Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No 169, Malang e-mail: rflyehezkiel@gmail.com Abstrak Penulis membahas urgensi pengaturan artificial intelligence kendaraan semi otonom dan otonom sesuai aspek keselamatan dan keamanan berkendara berbasis kecerdasan buatan berdasarkan hukum lalu lintas di Indonesia. Pemilihan isu dilatar belakangi adanya kekosongan hukum Undang-Undang Lalu Lintas dan Angkutan Jalan pada sektor pengujian kendaraan ini. Identifikasi rumusan masalah jurnal ini ialah urgensi pengaturan artificial intelligence dalam sektor kendaraan berbasis semi otonom dan otomatis di Indonesia sesuai aspek keamanan dan keselamatan berkendara serta bentuk pengaturan yang tepat mengenai regulasi kendaraan semi otonom dan otonom di Indonesia. Jenis penelitian ini adalah penelitian normatif menggunakan statue, comparative, dan conceptual approach. Urgensinya dilandaskan pada Alinea ke-empat Pembukaan UUD 1945 yaitu memajukan kesejahteraan umum dan Pasal 34 ayat 3 UUD 1945 yaitu memberi fasilitas umum yang layak. Tren kendaraan ini menjadikan kendaraan tersebut harus dikaji lagi untuk melindungi pengguna. Peraturan ini masih melindungi kendaraan konvensional sehingga terjadi kekosongan hukum Pasal 77 UU LLAJ dan Pasal 15 (2) PP No 37 Tahun 2017 tentang kendaraan ini. Mengacu pada peraturan kendaraan dari Amerika Serikat-Jerman sudah melindungi hak penggunanya dimulai dari pengujian fisik kendaraan independen, data kendaraan, pengawas dari lembaga khusus yang sebagian substansinya bisa dijadikan referensi untuk hukum Indonesia. Kata Kunci: artificial intelligence, kendaraan semi otonom-otonom, hukum lalu lintas Indonesia Abstract This research discusses the urgency of the regulation of artificial intelligence in semi-driverless and driverless vehicles according to safety and security aspects for artificial intelligence-based vehicles according to traffic law in Indonesia. This research topic departed from the legal loophole in traffic Law concerning Traffic and Road Transport in the testing sector for this type of vehicle. The application of safety and security of such vehicles, however, does not protect drivers, pedestrians, and the surroundings. The identification of the research problems in this research involves the urgency of artificial intelligence regulation in the sector of semi-driverless and driverless vehicles in Indonesia according to safety and security aspects in driving and proper regulations concerning semi-driverless and driverless vehicles in Indonesia. This research employed a normative method and statutory, comparative, and conceptual approaches. The urgency discussed refers to the fourth paragraph of the Preamble of the 1945 Constitution, mentioning general welfare, and Article 34 Paragraph 3 of the 1945 Constitution mentioning the provision of decent public facilities. The trend of these vehicles needs to be reviewed to protect their users. However, these regulatory provisions only protect conventional vehicles and this condition leaves a legal loophole in Article 77 of the Law concerning Traffic and Road Transport and Article 15 (2) of Government Regulation Number 37 of 2017 concerning these vehicles. To compare, the regulation of vehicles in the US and Germany protects the rights of the users, ranging from vehicle physical testing, data on vehicles, and supervision, to special institutions, where most of the substance of this regulation could serve as a reference for the law in Indonesia. Keywords: artificial intelligence, semi-driverless and driverless vehicles, traffic law in Indonesia